A rare autopsy case of traumatic rhabdomyolysis associated with intermittent assault. (May 2016) - Chiba, Fumiko; Makino, Yohsuke; Motomura, Ayumi; Inokuchi, Go; Ishii, Namiko; Torimitsu, Suguru; Hoshioka, Yumi; Abe, Hiroko; Yamaguchi, Rutsuko; Hashimoto, Mari; Sakuma, Ayaka; Nagasawa, Sayaka; et al.
Graphical abstract: Highlights: Fatal traumatic rhabdomyolysis typically involves severe blunt trauma. Fatal traumatic rhabdomyolysis typically takes an acute course. No fatal traumatic rhabdomyolysis without massive muscular injury has been reported. We report the first case of traumatic rhabdomyolysis appeared to have minor injury. Fatal traumatic rhabdomyolysis without severe muscular hemorrhage is a rare pitfall. Abstract: Traumatic rhabdomyolysis generally occurs after severe blunt trauma and is acute in onset, associated with severe disease, and potentially lethal. Accordingly, diagnosis of traumatic rhabdomyolysis in patients without massive subcutaneous or intramuscular hemorrhage is difficult, especially in the postmortem period, which is limited in terms of the availability of biochemical examination tools and accurate history of illness. To the best of our knowledge, there are no previous reports of death from traumatic rhabdomyolysis among individuals who did not pursue medical consultation. A previously healthy man in his early sixties had been punched and kicked several times in the previous 2 months, but he had not gone to a hospital. He suddenly lost consciousness at his workplace approximately 5 days after the most recent assault, and cardiopulmonary arrest occurred when the emergency service arrived. He died the same day, and a medicolegal autopsy was performed. Although several sites of minor subcutaneous and muscle hemorrhage were observed, the cause of death was unclear upon macroscopic assessment. Immunohistochemical staining revealed acute renal failure caused by rhabdomyolysis. We herein report a rare case of fatal traumatic rhabdomyolysis, seemingly associated with minor and apparently nonlethal muscle injury.